PENGEMBANGAN KAMPUNG WISATA BATIK KAUMAN SURAKARTA DENGAN PENGUATAN KARAKTER SEBAGAI KAMPUNG KONSERVASI - Deskarina, Rekta (Kepariwisataan: Jurnal Ilmiah, 2017)
Batik Tourist Village of Kauman has been established by the government to be the region with the priority of conservation handling in Surakarta. Kauman has great potentials such as cultural and architectural potential. As a cultural-based tourism village, its development is targeted in accordance with potential and characteristic that can be developed as interesting attraction without ignoring tradition and local culture values. This reseach aims to analyze the problems found in kauman and how to strengthen the character of kauman as a conservation area. The concept of area organizing on Batik Tourist Village of Kauman must not only be able to give spirit to the area (visitable) but also able to serve visitors and comfortable to visit (livable and walkable). The organizing guidance of Batik Tourist Village of Kauman is conducted by strengthening tourist attraction and the organizing of supporting facilities (access and amenity). This organizing guidance must not only be able to utilize the cultural heritage as tourist attraction but also be able give protection to the cultural heritage. Keywords: tourism village, culture-based tourism village, conservation area